Increasing Student Learning Motivation by Guidance and Counselling Teachers During the Covid-19 Pandemic - Monica, Mega Aria; Erlina, Nova; Azalia, Novela (Universitas Islam Negeri Raden Intan Lampung, 2021)
Motivation is an important thing in learning. During the current covid-19 pandemic, with many different learning patterns, it causes students to experience a decrease in learning motivation. The purpose of this study was to determine the role of guidance and counseling teachers in increasing student learning motivation during the covid-19 pandemic. This research uses a qualitative research type, with a case study research design. The results of the study show that the efforts of guidance and counseling teachers in increasing learning motivation are collaborating with subject teachers, homeroom teachers, and also information from parents of students.